Skuteczność polityk odstraszania w teatrze europejskim w świetle doświadczeń sojuszników USA doby wojny o Ukrainę i II zimnej wojny - Nycz, Grzegorz (Forms of Power in Contemporary World – Case Studies, 2023)
The chapter discusses the problem of adequacy of adopted and modified for the sake of XXI century capacities to defend NATO East flank (European Deterrence Initiative) in the context of the ongoing Russia-West crisis since 2014. Relations between the U.S. and Russia (with an impact on the outcome of the Ukraine contest) were to a large degree under a pressure of the post-Cold War arms control agreements, a part of which referring to intermediate range ballistic missiles and conventional forces were made inactive before the Russian aggression in Ukraine of 2022. Under the conditions of the crisis of the New Cold War the security policies of Western powers were subject to revision connected with the challenge to its liberal concept of international order, as well as in the light of the challenge to earlier balance of power in Europe formed under the leadership of the U.S. and NATO, sharply put into question by Russia. The chapter analyses the budgetary dimension of the Western defense aid to Ukraine and instruments of supporting NATO East flank with an eye on newly formed challenges in the time of Ukraine war, including a threat to European and international energy security.